PENGARUH METODE ASSESMENT PROSES KONTROL MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MELALUI PEMBELAJARAN - Sari, Siti Mayang; Fauzi, Chairul; Waruwu, Winning Amintas Kartika; Hasratuddin, Hasratuddin (Jurnal Ilmiah Aquinas, 2021)
Writing this article, it describes a process control assessment method that will improve students' critical thinking skills. This study uses a quantitative research method where data processing is based on multivariate analysis, where this method aims to find out how much influence the variables on an object, or in large numbers simultaneously or simultaneously. A control analysis process that results from the final grades of T / A students 2013-2019, is expected to get better and simultaneous learning value results, so that it will improve critical thinking skills for students. With regard to this value, it can be seen from the results of the process of statistical multivariate analysis based on the results of the final scores of five courses, namely: Indonesian Language, Learning Strategies, Aqidah Akhlak, Learning Psychology, and Early Childhood Education Development. Multivariant analysis reveal will that the process of assessing the results of data from student scores can be used as a reference for other students in different subjects, to be able to maintain their final score results by having the potential in learning innovation, namely having critical thinking skills and for eye-level lecturers. The lecture can see the level of student achievement in the last seven years.